The Difference Between the Essence of Fiqh Lughah and Arabic Linguistics in the Study of Arabic Language Education - Madani, Afdhalul; Abdul Rosyid; Rizky Syarif Al Rosyid; Iis Susiawati (Global Action and Education for Society, 2026)
This study aims to thoroughly describe and analyze the essence, scope, and essential differences between Fiqih Lughah and Arabic Linguistics. The background reveals that although the Arabic language holds a central role as the foundation of civilization and the language of the Qur'an, the understanding of Arabic linguistic terms often overlaps, potentially affecting learning outcomes. The method employed is Library Research (Studi Pustaka) with a qualitative approach, involving descriptive-analytical data analysis, including the interpretation and comparison of classical and contemporary literature. The findings indicate that some scholars equate Fiqhul-Lughah with ‘Ilmul-Lughah, which is often defined as encompassing synchronic, diachronic, and comparative studies. However, the key distinction lies in the focus: Fiqih Lughah has a broader scope, is historical-comparative, and treats language as an instrument for understanding culture and civilization. Conversely, ‘Ilm al-Lughah is descriptive-structural and studies language as the primary objective. The research concludes that the most accurate term for linguistics is ‘Ilm al-Lughah, while Fiqh al-Lughah is more relevantly equated with philology, the discipline that examines the authenticity and content of classical manuscripts.